The effects of geochemical processes on groundwater chemistry and the health risks associated with fluoride intake in a semi-arid region of South India. Issue 8 (29th January 2020) - Karunanidhi, D.; Aravinthasamy, P.; Deepali, M.; Subramani, T.; Roy, Priyadarsi D.
Abstract : This study attempts to establish the effects of subsurface geochemical processes based on the hydrogeochemical attributes of 61 well samples collected in a semi-arid region of South India. Abstract : This study attempts to establish the effects of subsurface geochemical processes based on the hydrogeochemical attributes of 61 well samples collected in a semi-arid region of South India. The study also provides the health risks associated with the consumption of fluoride-enriched groundwater by the rural people since groundwater is the major source of water supply in the Shanmuganadhi River basin. In this work, water–rock interaction diagrams, an entropy-weighted water quality index (EWQI), and health risk models as per the United States Environmental Protection Agency (USEPA) were prepared to understand the geochemical mechanism behind the groundwater chemistry and its role in impacting health. About 72% of these samples are of mixed Ca 2+ –Mg 2+ –Cl − water type, representing a transition from freshwater to brackish water, and 36% of them have fluoride above the permissible limit (>1.5 mg l −1 ). An evaluation of the hydrogeochemical attributes suggests that silicate weathering, carbonate dissolution and reverse ion exchange mostly control the hydrochemistry of the groundwater. The EWQI characterizes about 30% of these samples as unsuitable for drinking and another 49% as of moderate quality. Human health risks were evaluated by dividing the population into seven different age groups and estimating the hazard quotient (HQ) and total hazard index (THI) from intake and dermal contact with fluoride-rich groundwater. The groundwater of this region poses a higher risk for the younger population compared to the adults. About 79% of these groundwater samples pose a health risk to 5–12 month-old infants and only 36% of the samples could be potentially hazardous for adults >23 years old. Our results suggest that the ADDdermal pathway indicates less risk compared to the ADDintake estimations.